Chinese mining investment projects in Arctic - Pierre-Louis Têtu; Frédéric Lasserre (Département de sociologie, Université Laval, 2017)
China, the world’s largest importer of raw materials since the beginning of the 21st century, is keeping a watchful eye on the mining potential of the Arctic. Chinese foreign direct investment (FDI) in mining projects in the Canadian Arctic, Northern Quebec and Greenland have contributed to a certain sinophobia, due in part to a lack of understanding of the factors determining the choice of this region for these investments. The results show that these territories are attractive because of their political stability and competitive business climate as well as the quality of their physical resources. Nonetheless, this attractiveness is diminished by a lack of infrastructure in the Arctic as well as the high cost and reduced availability of labour. La Chine, premier importateur mondial de matières premières depuis le début du 21e siècle, est attentive au potentiel minier de l’Arctique. Des investissements directs à l’étranger (IDE) chinois dans des projets miniers dans l’Arctique canadien, le Grand Nord québécois et au Groenland ont contribué à faire naître une certaine sinophobie, en raison notamment de la méconnaissance des facteurs qui déterminent le choix de cette région pour ces investissements. Les résultats démontrent que ces territoires sont attrayants en raison de la stabilité politique et du climat compétitif des affaires qui les caractérisent, ainsi que de la qualité de leurs ressources physiques. En revanche, le manque d’infrastructures dans l’Arctique et le coût et la disponibilité de la main-d’oeuvre constituent des facteurs limitatifs.